Pengaruh Kecerdasan Emosional, Kompensasi, Budaya Organisasi Dan Motivasi Kerja Terhadap Komitmen Organisasi Karyawan PT. Surya Andola Kota Metro - Ardiyansah, Feri; Widodo, Deny Edy (Jurnal Manajemen DIVERSIFIKASI, 2022)
ABSTRACT This study aims to determine the effect of emotional intelligence, compensation, organizational culture and work motivation on the organizational commitment of employees of PT. Indo Metro Surya Andola Metro City. By distributing questionnaires in the form of questions about emotional intelligence, compensation, organizational culture and work motivation on organizational commitment. then processed with SPSS 21 with the classical assumption test approach with the methods of normality, linearity, homogeneity. This study uses quantitative methods with multiple linear regression analysis, partial test, F test, determination to determine the effect of emotional intelligence, compensation, organizational culture and work motivation on organizational commitment of employees of PT. Indo Metro Surya Andola. The results of the partial study show that simultaneously emotional intelligence, compensation, organizational culture and work motivation have a positive and significant effect on organizational commitment. Keywords: Emotional Intelligence, Compensation, Organizational Culture, Work Motivation, Organizational Commitment